2017
DOI: 10.1038/srep44841
|View full text |Cite
|
Sign up to set email alerts
|

Mevalonate Cascade Inhibition by Simvastatin Induces the Intrinsic Apoptosis Pathway via Depletion of Isoprenoids in Tumor Cells

Abstract: The mevalonate (MEV) cascade is responsible for cholesterol biosynthesis and the formation of the intermediate metabolites geranylgeranylpyrophosphate (GGPP) and farnesylpyrophosphate (FPP) used in the prenylation of proteins. Here we show that the MEV cascade inhibitor simvastatin induced significant cell death in a wide range of human tumor cell lines, including glioblastoma, astrocytoma, neuroblastoma, lung adenocarcinoma, and breast cancer. Simvastatin induced apoptotic cell death via the intrinsic apoptot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 93 publications
(110 reference statements)
4
112
0
Order By: Relevance
“…In these studies, INS-1 832/13 cells were incubated in the absence (diluent]) or presence of simvastatin (0-30 µM) and FTI-277 (15 µM) for different time intervals as described in the text. Earlier studies have demonstrated that both of these agents, in the stated concentration range, significantly inhibited MVA and protein prenylation pathways in a variety of cells, including the islet β-cell [16, 17, 19-22]. …”
Section: Methodsmentioning
confidence: 99%
“…In these studies, INS-1 832/13 cells were incubated in the absence (diluent]) or presence of simvastatin (0-30 µM) and FTI-277 (15 µM) for different time intervals as described in the text. Earlier studies have demonstrated that both of these agents, in the stated concentration range, significantly inhibited MVA and protein prenylation pathways in a variety of cells, including the islet β-cell [16, 17, 19-22]. …”
Section: Methodsmentioning
confidence: 99%
“…In addition to a wide range of tumor cells, we have shown that Simva (10 lM) induces cell death in primary human airway mesenchymal cells and primary human atrial fibroblasts via the intrinsic apoptotic pathway [20,29,67]. In GBM cells, we show that Simva, TMZ, and Simva/TMZ combination induced intrinsic apoptotic cell death, with Simva/TMZ inducing significantly more apoptosis when compared to the singular treatments ( Fig.…”
mentioning
confidence: 74%
“…In line with our findings, Yanae et al 55 showed that statins inhibit cell proliferation and increase caspase-3 activity indicating apoptosis in C6 glioma cells. These effects were reversed by the addition of GGPP but not FPP 7. A cohort study evaluated the influence of simvastatin use on survival of 339 patients with GBM and showed that long-term prediagnostic statin use may improve survival following GBM (a reduced HR of death (0.79; 95% CI 0.63 to 1.00)).…”
Section: Statins and Gbm Cancer Therapymentioning
confidence: 99%